1995
DOI: 10.3133/ofr95191
|View full text |Cite
|
Sign up to set email alerts
|

Water-quality assessment of the Albemarle-Pamlico drainage basin, North Carolina and Virginia: Characterization of suspended sediment, nutrients, and pesticides

Abstract: The mission of the U.S. Geological Survey (USGS) is to assess the quantity and quality of the earth resources of the Nation and to provide information that will assist resource managers and policymakers at Federal, State, and local levels in making sound decisions. Assessment of water-quality conditions and trends is an important part of this overall mission. One of the greatest challenges faced by waterresources scientists is acquiring reliable information that will guide the use and protection of the Nation'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Atmospheric wet and dry deposition (Walker et al 2000;Whitall et al 2002), groundwater (Harned et al 1995), estuarine sediments (Giffin and Corbett 2003), and partial denitrification (Glibert 1988) are all potential sources that must be addressed in future research to determine the source contributions of the striking increases in NH concentration that were docu-ϩ 4 mented in both the Neuse and Cape Fear systems, and to further evaluate the overall importance of NH in driving ϩ 4 phytoplankton production and bloom formation (Fan et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Atmospheric wet and dry deposition (Walker et al 2000;Whitall et al 2002), groundwater (Harned et al 1995), estuarine sediments (Giffin and Corbett 2003), and partial denitrification (Glibert 1988) are all potential sources that must be addressed in future research to determine the source contributions of the striking increases in NH concentration that were docu-ϩ 4 mented in both the Neuse and Cape Fear systems, and to further evaluate the overall importance of NH in driving ϩ 4 phytoplankton production and bloom formation (Fan et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen attributable to upland agriculture and other human sources has been reported in estuaries and nontidal tributaries of the Mid‐Atlantic region of the U.S. since at least the 1960s (Brehemer, 1964; Harned et al. , 1995; Ator et al.…”
Section: Description Of Study Areamentioning
confidence: 99%
“…Nitrogen attributable to upland agriculture and other human sources has been reported in estuaries and nontidal tributaries of the Mid-Atlantic region of the U.S. since at least the 1960s (Brehemer, 1964;Harned et al, 1995;Ator et al, 2005a). Biological productivity in most temperate estuaries is nitrogenlimited (Vitousek et al, 1997), and excess nitrogen has contributed to damaging algal blooms (Brehemer, 1964;U.S.…”
Section: Description Of Study Areamentioning
confidence: 99%
“…Whether the DRAINMOD method is overpredicting runoff volume on artificially drained sites or the Curve Number method is underpredicting runoff for naturally drained conditions is unknown at this time. It is interesting to note, however, that water quality studies done on the Albermarle–Pamlico Drainage Basin examining various watersheds grouped according to land use, drainage characteristics, and surficial geology have shown that the highest surface water P concentrations were observed in agricultural Coastal Plain basins with medium to poor drainage (Harned et al, 1995; McMahon and Harned, 1998). It is not known whether these increased concentrations of P in surface waters stem from P in drainage waters or surface runoff on these sites.…”
Section: Resultsmentioning
confidence: 99%